The development of peripheral fatigue and short‐term recovery during self‐paced high‐intensity exercise - Froyd, Christian; Millet, Guillaume Y.; Noakes, Timothy D. (The Journal of physiology, 2013)
Key points In this study we describe the time course of fatigue development during and after an intense bout of self‐paced, high‐intensity dynamic exercise using various electrical stimulation parameters to assess neuromuscular function (NMF) changes. Most of the decrease in muscle function occurs within the first 40% of the exercise bout, and substantial recovery in muscle function occurs within 1–2 min after exercise termination. Decreases in muscle function varied greatly with different methods of stimulation, suggesting that the extent to which muscle fatigue is documented during exercise depends upon NMF assessment methodology. Measurements of muscle function must be performed as soon as possible after exercise termination, and previous studies may have underestimated the extent to which muscle fatigue develops during exercise. The time course of muscular fatigue that develops during and after an intense bout of self‐paced dynamic exercise was characterized by using different forms of electrical stimulation (ES) of the exercising muscles. Ten active subjects performed a time trial (TT) involving repetitive concentric extension/flexion of the right knee using a Biodex dynamometer. Neuromuscular function (NMF), including ES and a 5 s maximal isometric voluntary contraction (MVC), was assessed before the start of the TT and immediately (<5 s) after each 20% of the TT had been completed, as well as 1, 2, 4 and 8 min after TT termination. The TT time was 347 ± 98 s. MVCs were 52% of baseline values at TT termination. Torque responses from ES were reduced to 33–68% of baseline using different methods of stimulation, suggesting that the extent to which peripheral fatigue is documented during exercise depends upon NMF assessment methodology. The major changes in muscle function occurred within the first 40% of exercise. Significant recovery in skeletal muscle function occurs within the first 1–2 min after exercise, showing that previous studies may have underestimated the extent to which peripheral fatigue develops during exercise.